The effects of industrialized building system (IBS) application in increasing the efficiency of building construction projects / Eiman Haqim Abu Bakar and Rashidah Jimi Sham - Abu Bakar, Eiman Haqim; Jimi Sham, Rashidah (College of Built Environment, 2023)
In today's world, the construction sector is seen as a critical industry for boosting economic growth in both emerging and established countries.